HAK PARATE EKSEKUSI PADA KREDITUR TERHADAP JAMINAN DEPOSIT DARI DEBITOR PAILIT (ANALISIS PUTUSAN PENGADILAN NIAGA JAKARTA PUSAT NOMOR 23/PDT.SUS.PAILIT/2017/PN NIAGA JKT.PST. JO. PUTUSAN MAHKAMAH AGUNG NOMOR 243 PK/PDT.SUS-PAILIT/2018) - Clarissa Aurelie; Mia Hadiati (Jurnal Hukum Adigama, 2021)
The consequences of the bankrupt debtor brings considerable losses to his creditors. There are : preferred creditors, unsecured creditors, and separatist creditors. Since the date the debtor is declared bankrupt, the curator is in charge of all the assets of the debtor and determines the credits amount to pay the creditors, except for separatist creditors. As the separatist creditor, has the preferred position of other creditors to get paid first and also to execute specific guarantees by their own through parate executie. This thesis will aim to analyze and explain how the implementation of the parate executie for creditor to disbursement the deposit guarantee and  how the legal protection for creditors receiving deposit guarantee based on a case study PT. Plaza Indonesia and PT. Gagan Indonesia. The study belongs to normative legal research, using secondary data as the source. Technique of analyzing data employed by the research was a qualitative method. Based on the result of research, it can be explained that application of the parate executie is given by law to creditors who own a certificate of material security based on Article 55 of Law no. 37 of 2004 on Bankruptcy states. However, the execution cannot be conducted by unsecured creditors. PT. Plaza Indonesia in this case is an unsecured creditors. Even though the  creditor holds a deposit guarantee in the form of cash, without issuing a certificate as evidence, the creditor remains as an unsecured creditor. Therefore PT.Plaza Indonesia will get paid on a pro rata basis.